2021
DOI: 10.18502/aacc.v7i4.7630
|View full text |Cite
|
Sign up to set email alerts
|

Cancellation of Elective Surgeries in A Tertiary Care Hospital in North India

Abstract: Background: Cancellation of elective surgical treatments is a quality-of-care issue as well as a huge waste of health-care resources. Patients may experience emotional distress as a result of this, as well as difficulty for their families. Aim: To find the significant reasons of cancellation of scheduled surgical cases. Methods: A total of 300 elective operations in our institution were chosen. The completed surgeries were planned on the scheduled operation day, and the anaesthesiologist noted down a lis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…7 The results of a research done in India by Farooq and Mir revealed that it was roughly 20% of the consular rate, with the greatest rate being associated to the orthopedic department, which did not agree the findings of the current study. 8 According to the findings of this study, the highest proportion of surgery cancellations occurred in the ENT specialty in February 2018 (25%) and September 2019 (14%) respectively. Cancels are more common in general surgery, but the ratio of them to the number of procedures scheduled is greater in the ENT specialty.…”
Section: Discussionmentioning
confidence: 64%
“…7 The results of a research done in India by Farooq and Mir revealed that it was roughly 20% of the consular rate, with the greatest rate being associated to the orthopedic department, which did not agree the findings of the current study. 8 According to the findings of this study, the highest proportion of surgery cancellations occurred in the ENT specialty in February 2018 (25%) and September 2019 (14%) respectively. Cancels are more common in general surgery, but the ratio of them to the number of procedures scheduled is greater in the ENT specialty.…”
Section: Discussionmentioning
confidence: 64%
“…The finding of this study is higher compared with the study conducted in Ethiopia with meta-analysis 21.4% [ 25 ] St. Paul’s Hospital, Addis Ababa (8.9%) [ 26 ], Saudi Arabia (7.6%) [ 27 ], Zambia 18.8% [ 28 ], Sudan (20.2%) [ 29 ], America (4.4%) [ 30 ], Brazil (6.8%), German (12.7%), Wales (7.6%), New Delhi (17.6%), India (16.49% [ 31 ]. This discrepancy may be due to the fact that there are differences in sociodemographic characteristics, sample size, study area, and methodology.…”
Section: Discussionmentioning
confidence: 99%